2021
DOI: 10.3390/s21165382
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Practical Impacts of Using Single-Antenna and Dual-Antenna GNSS/INS Sensors in UAS-Lidar Applications

Abstract: Data collected from a moving lidar sensor can produce an accurate digital representation of the physical environment that is scanned, provided the time-dependent positions and orientations of the lidar sensor can be determined. The most widely used approach to determining these positions and orientations is to collect data with a GNSS/INS sensor. The use of dual-antenna GNSS/INS sensors within commercial UAS-lidar systems is uncommon due to the higher cost and more complex installation of the GNSS antennas. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Then, the heading angle ϕ GNSS U of the dual antennas can be calculated by the single baseline difference method [19] and directly output by the GNSS.…”
Section: Calibration Methods Of Installation Error Angle In Headingmentioning
confidence: 99%
“…Then, the heading angle ϕ GNSS U of the dual antennas can be calculated by the single baseline difference method [19] and directly output by the GNSS.…”
Section: Calibration Methods Of Installation Error Angle In Headingmentioning
confidence: 99%
“…Due to their extensive capabilities, GNSS/INS systems are primarily used in navigation and transport applications. These include tests using Unmanned Aerial Vehicles (UAV) [8][9][10] and Unmanned Surface Vehicles (USV) [11,12], locating mobile phones [13], indoor [14], terrestrial [15] and space [16] navigation, geodetic [17][18][19] and hydrographic surveys [20][21][22], operating Autonomous Ground Vehicles (AGV) [23][24][25], rail transport, in particular for the purposes of High-Speed Rail (HSR) [26,27], road transport [28][29][30] or preventing intentional interference [31,32].…”
Section: Hydrographic Surveys Are Among the Navigation Applications That Commonly Use Global Navigation Satellite Systems (Gnss) Accordinmentioning
confidence: 99%
“…Measurements carried out indicated that the position error did not exceed 15 m. Inertial navigation systems are commonly used in navigation and transport applications. The most important of them include: tests using Autonomous Ground Vehicles (AGV) [22][23][24], Unmanned Aerial Vehicles (UAV) [25][26][27] and Unmanned Surface Vehicles (USV) [28,29]; locating mobile phones [30], indoor [31], terrestrial [32] and space [33]; navigation, geodetic [34][35][36] and hydrographic surveys [37][38][39]; and rail transport [40,41] and road transport [42][43][44]. Moreover, they are used in the case of preventing intentional interference [45,46] and in urban areas in which the multipath effect occurs [47][48][49].…”
Section: Introductionmentioning
confidence: 99%